Changes in aromatic characteristics of loureiro and alvarinho wines during maturation - Oliveira, J. M. (2008)
Changes in volatiles during maturation in bottles of monovarietal Vinhos Verdes wines from Loureiro and Alvarinho grape varieties, were followed by chemical and sensory analyses. Young wines and wines matured for 8 and 20 months were studied. The volatiles were determined by gas chromatography– mass spectrometry (GC-MS) after extraction on XAD-2 resin. Straight chain fatty acid ethyl esters and acetates of fusel alcohols decreased quicker for Loureiro wine, while the increase in ethyl esters of branched fatty acids was similar for both varieties. Linalool, Ho-trienol, a-terpineol and b-damascenone could be used to differentiate between each variety. However, linalool decreased to negligible values after 20 months of maturation. b-Damascenone decreased but remained high enough to be useful for differentiating each variety. Sensory analysis indicated a decrease of tropical fruit and tree fruit characters with conservation time for Alvarinho wine, and the opposite for Loureiro; moreover, citrus fruit character decreased in both varieties